Physical Activity on Coronary Heart Disease Patients - Merbawani, Raras (Kirana Publisher (KNPub), 2022)
Lack of physical activity is associated with weight gain, being overweight and obesity which are the main factors causing modern diseases such as coronary heart disease. It is estimated that during the last 15 years, 8.7 million of the world's population have died from coronary heart disease, an increase of 12.2% from 2000. Regular physical activity can reduce the risk of morbidity and mortality of all risks of cardiovascular disease including coronary heart disease. This study aims to describe physical activity in patients with coronary heart disease. The research design used in this study is descriptive with a retrospective approach. The population in this study were all patients with coronary heart disease at Cardiology Departement in Hospital Dr. Wahidin Sudiro Husodo for the period July 2018. The sample size was 102 respondents using Consecutive Sampling techniques. This research was conducted on 2-14 July 2018. The results of this study indicate that almost half of respondents with low intensity of physical activity were 50 people (49.0%)